Jurisdiction Over A Person Abducted From A Foreign Country: Alvarez Machain Case Revisited - Khin Maung Sein, Abdul Ghafur Hamid (Journal of Malaysian and Comparative Law, 2019)
Unless a State is prepared to try a person in absentia, the exercise of enforcing jurisdiction over individuals depends on their physical presence in the territory of the State seeking to exercise jurisdiction. There have been several cases where an individual has been abducted forcibly from the territory of one State to be tried in another. In such cases, the question which arises is whether the abduction bars a court from exercising jurisdiction.